Dental care for hearing impaired patient using the Hand Talk® brazilian sign language application: Na experience report (Research, Society and Development, 2024)
Special needs patients show biological, physical, mental and social alterations making the dental treatment difficult, which requires a specific protocol for treatment. This paper aims at reporting the experience of dental treatment of hearing impaired, performed by the Dental Specialties Center (CEOII), in a large county in the state of Santa Catarina, Southern Brazil. True the mobile application Hand Talk® a text message to BRAZILIAN SIGN LANGUAGE translator, the dentist and the patient were able to communicate directly without the need for a BRAZILIAN SIGN LANGUAGE translator. Observed that treating a hearing impaired patient is a challenge as the majority of professionals they are not versed in BRAZILIAN SIGN LANGUAGE. However, the use of Hand Talk® enabled their communication making it possible for the patient to express his main complaint and his expectations regarding the treatment. Furthermore, this technology proved to be use friendly and is available free of chare.